Dendrimers and hyperbranched structures for biomedical applications. (October 2019) - Pedziwiatr-Werbicka, Elzbieta; Milowska, Katarzyna; Dzmitruk, Volha; Ionov, Maksim; Shcharbin, Dzmitry; Bryszewska, Maria
Graphical abstract: Highlights: Dendrimers are hyperbranched polymers. >100 types of dendrimers have been synthesized. 5 most common families are described. Dendrimers can deliver drugs. Dendrimers can improve the bioavailability of drugs. Abstract: The use of nanotechnology in biology and medicine has been marked by rapid progress of these industries due to the emergence of new devices, supramolecular systems, structures, complexes and composites. One striking example of nanotech polymers is dendrimers. Their structure is formed by branches of monomeric subunits diverging in all directions from the central core. In choosing monomers and functional groups in synthesis, one can precisely set the properties of the resulting macromolecules. Currently, with modifications, >100 types of dendrimers have been synthesized. Of these, the 5 most common families can be distinguished: (i) Polyamidoamine (PAMAM) dendrimers are based on the ethylenediamine core and their branches are constructed from methyl acrylate and ethylene diamine. Currently, there is a large selection of PAMAM dendrimers with surface groups of many types. (ii) Polypropyleneimine (PPI) dendrimers are based on a butylenediamine core and polypropyleneimine monomers. In addition to PPI, the second popular abbreviation of these dendrimers is DAB (diaminobutyl) – from the name of the nucleus. Currently commercially available are (iii) Phosphorus dendrimers. In phosphorus dendrimers, phosphorus atoms are present in the core and branches of the dendrimer. (iv) Carbosilane dendrimers are based on a silicon core and have ammonium or amino groups on the periphery. (v) Poly(lysine) and poly(L-ornithine) dendrimers are a dendrimeric structure composed of amino acids residues. Characteristic surface groups possessing hydrophobic or hydrophilic components help to encapsulate the ligands inside or attach them to the surface, ensuring protection from degradation. Drug molecules complexed with dendrimer can be delivered to target cell where they are released from the complex. Dendrimers can improve the bioavailability of drugs by increasing their solubility in water, and changing surface charge, thereby reducing toxicity. In this review, the properties of dendrimers as drug carriers are discussed.